FE Analysis on the Interconnection between Bending and Corrosion-Induced Cracks - Thorsson, Jonathan (My University, 2023)
Reinforced concrete structures degrade due to carbonation or chloride-induced cor rosion. As these structures age, understanding corrosion-induced damage becomes more important. When reinforcement within concrete corrodes, it generates corro sion products that occupy more space than the original steel. Confined within theconcrete, these products exert pressure, causing stress accumulation and subsequent cracking. Previous investigations on pitting corrosion and formation of longitudinalcracks in reinforced concrete beams have yielded inconsistent results, highlighting the uncertain relationship between pitting corrosion and corrosion-induced cracks. While some studies have used finite element analysis to assess concrete cracking caused by corrosion, few have explored the consequences of reinforced concrete beams undergoing imposed deformation during the corrosion process. This the sis presents non-linear finite element analyses of crack patterns and crack widths in a reinforced concrete beam experiencing chloride-induced corrosion and imposed deformation, including bending cracks. The results are compared with experimental data. The analysis considers different types and degrees of corrosion distribution,as well as varying the volume expansion of corrosion products. The finite element analyses successfully replicated the observed corrosion-induced crack pattern on thebeam’s lateral side. Corrosion induced cracks initiated both at the bending cracks, and between the bending cracks when both uniform and pitting corrosion was con sidered. When pitting corrosion was removed or kept constant, corrosion induced cracks was initiated primarily between the bending cracks. Pitting corrosion was identified as a factor that increased longitudinal crack widths at the pit location, with its influence diminishing further away. Moreover, the analysis supported theexperimental results, that the most corroded section does not necessarily result in the largest crack widths. Additionally, it revealed the non-linear effects of volumeexpansion and change in crack widths. A small increase in volume expansion could lead to a significant increase in crack widths and crack widths could increase moreat one location and less in others. The FE analysis did reproduce the linear crack growth observed in the experiment when the crack widths are small. Future workshould focus on including more test data with varying levels of imposed deformation and examining corrosion rate, corrosion product dissipation, and the impact of stir rups on corrosion-induced cracking. Additionally, running less varied FE analyses inscenarios where the bending cracks and pit locations are more controlled can provide valuable insights into their effect on measured crack widths.
Keywords: Reinforced concrete structures, finite element analysis, chloride-induced corrosion, crack pattern, crack width, corrosion distribution, volume expansion